Androgen Modulates Functions of Endothelial Progenitor Cells through Activated Egr1 Signaling. (30th November 2015) - Ye, Yizhou; Li, Xizhe; Zhang, You; Shen, Zhenya; Yang, Junjie
Abstract : Researches show that androgens have important effects on migration of endothelial cells and endothelial protection in coronary heart disease. Endothelial progenitor cells (EPCs) as a progenitor cell type that can differentiate into endothelial cells, have a critical role in angiogenesis and endothelial protection. The relationship between androgen and the functions of EPCs has animated much interest and controversy. In this study, we investigated the angiogenic and migratory functions of EPCs after treatment by dihydrotestosterone (DHT) and the molecular mechanisms as well. We found that DHT treatment enhanced the incorporation of EPCs into tubular structures formed by HUVECs and the migratory activity of EPCs in the transwell assay dose dependently. Moreover, microarray analysis was performed to explore how DHT changes the gene expression profiles of EPCs. We found 346 differentially expressed genes in androgen-treated EPCs. Angiogenesis-related genes like Egr-1, Vcan, Efnb2, and Cdk2ap1 were identified to be regulated upon DHT treatment. Furthermore, the enhanced angiogenic and migratory abilities of EPCs after DHT treatment were inhibited by Egr1-siRNA transfection. In conclusion, our findings suggest that DHT markedly enhances the vessel forming ability and migration capacity of EPCs. Egr1 signaling may be a possible pathway in this process.